The Effect of Marketing Mix In “Yuk Gi Nyelik Pasien (YGNP) “ Program on The Level of Satisfaction and Public Trust to The Government of East Belitung Regency - Rachim, Abdul; Nurjanah, Siti; Simangungsong, Fernandes; Sentosa, Ilham; Agung, Syahrum (International Journal of Educational Technology and Artificial Intelligence, 2024)
This study aims to analyze the effect of marketing mix on the “Yuk Gi Nyelik Pasien” program on the level of satisfaction and public trust in the Regional Government of East Belitung Regency. Marketing mix in this context includes product, price, place, promotion, people, process, and physical evidence. The research method used is multiple regression to process data obtained from a survey of East Belitung people who enjoy the program. The results showed that through the approach of the components of the Marketing Mix in Local Government Policy simultaneously had a significant influence on public satisfaction and trust in the Local Government. Partially, each component of the marketing mix also shows a varying influence on the dependent variable. This study concludes that through the marketing mix approach in the “Yuk Gi Nyelik Pasien” program can increase public satisfaction and trust in the Regional Government of East Belitung Regency with a very significant and simultaneous effect. Marketing Mix Government Policy Yuk Gi Nyelik Pasien Program has a stronger influence on Public Trust than Public Satisfaction. The practical implication of this research is the need for the East Belitung Regency Government to take a Marketing Mix approach in running local government programs so as to provide public satisfaction and trust and strengthen the relationship between the Local Government and the community and improve public services.